From superphanes to beltenes - Gleiter, Rolf; Hellbach, Björn; Stäb, Silke; Schaller, Rolf (Pure and applied chemistry, 2006)
This short review describes paths to superphanes with metal-stabilized cyclobutadiene and cyclopentadienone rings in a one-pot and stepwise fashion. The stepwise synthesis also led to a new class of belt-like systems with large rings composed of CpCo-stabilized cyclobutadiene rings connected with propane chains. Finally, our research yielded the first beltenes composed of alternating four- and eight-membered conjugated rings.